Językowy obraz świata w tekstach Jana Jakuba Rousseau. „Wyznania” jako narracyjne konstruowanie tożsamości - Anna Wasilewska (Problemy Wczesnej Edukacji)
In this text I have taken up a reflection upon one of the most important works by J.J. Rousseau, “Confessions”. The book is considered to belong to personal literature, so I treated it as an autobiographical narration. In the methodological research I used both the category of a linguistic view of the world and the category of constructing an identity in the linguistic and cognitive analysis. On the one hand Rousseau’s work can be considered as an autobiographical narrative, but on the other hand it can be treated as fiction. And it is the dualism of construction that allows the interpretation of the text in many ways, formal or poetic, as well as referring to the writer’s life. I recommend reading Rousseau’ s biography again in order to see the intersection of history and fictitious reality, to reconstruct the linguistic strategy of giving meaning by J.J. Rousseau in constructing “Confessions” as well as in constructing identity.